TRANSFORMATIONAL PROPHETIC SUFISTIC EDUCATION: A STUDY OF THE APPLICATION OF IMAM AL-GHAZALI AT VOCATIONAL SCHOOL - Atiqullah; Masrurah; Abd Mannan; Habiburrahman; Ismi Noerul Izzah (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2025)
The rapid advancement of technology should be balanced with a strong moral education. Nowadays, many children lack proper religious education within their families. Moreover, the progress of science and technology has negatively impacted the development of children and adolescents. Sufistic prophetic education serves as an alternative model for education practitioners to rebuild students' character in educational institutions. This study uses a descriptive qualitative method. The results show that the developed Sufistic prophetic model is characterized by an ethical Sufistic approach through the Naqshabandiyah Mudhariyah tariqa program, which has traditionally evolved since the time of Mursyid Kyai Wahid Khudaifah, the founder of the Darul Ulum Islamic boarding school. The activities and stages in the practice of the Naqshabandiyah Mudhariyah tariqa include tazkiyat al-nafs (self-purification), mujahadah (spiritual striving), riyadhah (spiritual discipline), dhikrullah (remembrance of God), maqamat (spiritual stations), and ahwal (spiritual states). The implementation involves recitations of asmaul husna (names of God), prayers, and istighosah (supplications), separation of classes, allegiance to the tariqa, and tawajjuh (focus). Several supporting and inhibiting factors in the implementation have been identified.